Gotier and Thyrotoxicosis in Sulaimani - Hasan, Faruk (Sulaimani Journal for Pure and Applied Sciences, 2001)
The aim of this retrospective study was to elucidate the characteristics of the patients with goiter in Sulaimani teaching hospital. A total of 140 patients entered this study The mean age was 30 years. The female : male ratio was 4:1, and 2/3'd of females were housewives and about 2/3'd of males were self-employed. About half of the cases had goiter of more than a year and 1/3'd of the cases had a positive family history of goiter. Lipidol was a significant factor in the development of thyrotoxicosis . 10% of the cases had emotional upheavals preceding thyrotoxicosis. In conclusion :Goiter is increasing in Sulaimani territory with an increasing costs on the governments and the local health services which requires extra-ordinary steps for propaganda and education to encourage people to use iodized table salts routinely to prevent the disease. The increased incidence of thyrotoxicosis in this area is multifactorial including the very stressful life-style of the people in this mountainous area and the sudden introduction of lipidol to patients with avid, enlarged thyroid gland , and on the top of that the changes in the diet patterns due to sudden opening of free markets in the recent years all might be contributory factors.
Keywords: FH Goiter and Thyrotoxicosis in Sulaimani Kurdistan Region Iraq